2019
DOI: 10.1002/path.5365
|View full text |Cite
|
Sign up to set email alerts
|

Making sense of giant cell lesions of the jaws (GCLJ): lessons learned from next‐generation sequencing

Abstract: Next-generation sequencing has revealed mutations in several bone-related lesions and was recently used to uncover the genetic basis of giant cell lesions of the jaws (GCLJ). Consistent with their benign nature, GCLJ show a low tumor mutation burden. They also harbor somatic, heterozygous, mutually exclusive mutations in TRPV4, KRAS, or FGFR1. These signature mutations occur only in a subset of lesional cells, suggesting the existence of a 'landscaping effect', with mutant cells inducing abnormal accumulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 93 publications
2
32
0
1
Order By: Relevance
“…Recently, KRAS , TRPV4, and FGFR1 gain‐of‐function mutations were reported by our group in central and peripheral giant cell lesions of the jaws 8 . Following this work, KRAS and FGFR1 mutations have been shown to also occur in non‐ossifying fibromas of bones, 9 reinforcing the speculation that these lesions might represent the same entity 10‐12 . KRAS mutations have also been reported in implant‐associated peripheral giant cell granuloma 13 .…”
Section: Introductionsupporting
confidence: 58%
See 3 more Smart Citations
“…Recently, KRAS , TRPV4, and FGFR1 gain‐of‐function mutations were reported by our group in central and peripheral giant cell lesions of the jaws 8 . Following this work, KRAS and FGFR1 mutations have been shown to also occur in non‐ossifying fibromas of bones, 9 reinforcing the speculation that these lesions might represent the same entity 10‐12 . KRAS mutations have also been reported in implant‐associated peripheral giant cell granuloma 13 .…”
Section: Introductionsupporting
confidence: 58%
“…Giant cell lesions of the jaws occur in genetic syndromes caused by RAS mutations, such as Noonan syndrome, cardio‐facio‐cutaneous syndrome, Leopard syndrome, oculoectodermal syndrome, and Schimmelpenning syndrome (reviewed by ref. 12 ). Additionally, these lesions can occur in osteoglophonic dysplasia, which results from FGFR1 mutations 12,14 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,31,32 Importantly, studies have unveiled that the pathogenesis of a subgroup of CGCG seems to be closely related to the pathogenesis of nonossifying fibroma of long bones, as both lesions share MAPK pathway-activating mutations. 33 Immunohistochemistry using calcitonin and glucocorticoid receptors as a tool for choosing the optimal treatment in cases of CGCG has been widely reported in the literature. [9][10][11] Nogueira et al 10 suggested that CGCG with a good response to glucocorticoids may have a median Hscore of 142 for glucocorticoids in the mononuclear component and of 48 in the multinucleated giant cells.…”
Section: Discussionmentioning
confidence: 99%